2020
DOI: 10.1177/0192512120963883
|View full text |Cite
|
Sign up to set email alerts
|

Capacity building for proportionate climate policy: Lessons from India and South Africa

Abstract: Countries must develop their capacity to credibly revise their nationally determined contributions (NDCs) proportionate to the global climate goal. This paper argues that long-lasting capacity is necessarily embedded in the institutions governing cooperation between state and non-state actors. This institutional capacity for cooperation is determined by the two interactive processes of conception and calibration, where the state plays a definitive role in mediating between competing interests. In conception, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The contributions to this special issue showed that the design of institutions is important for producing proportionate climate policy responses. If the state institutions lack capacity and cannot mediate between competing private interests or are even ‘captured’ by these (see Kalinowski, 2020), the likely outcome are policy underreactions (see Upadhyaya et al, 2020), which also holds true for international climate politics (see Castro, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions to this special issue showed that the design of institutions is important for producing proportionate climate policy responses. If the state institutions lack capacity and cannot mediate between competing private interests or are even ‘captured’ by these (see Kalinowski, 2020), the likely outcome are policy underreactions (see Upadhyaya et al, 2020), which also holds true for international climate politics (see Castro, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Shearer et al (2016) suggest extending this list of explanatory variables to networks, as we do here. Consequently, this special issue is interested in furthering our understanding of how institutions, interests, ideas, and networks affect climate politics and the corresponding climate policy outputs (see, in particular, Carter and Little, 2020; Leiren et al, 2020) and outcomes (see, in particular, Kalinowski, 2020; Upadhyaya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Balancing the goals of development and climate action in an equitable and socially-just manner is particularly important, but also challenging for these countries (Sforna, 2019). Thus, this journal invites analyses of climate action especially from the perspective of developing countries (e.g., Zimmer et al, 2015) and emerging market economies (e.g., Solorio, 2021;Upadhyaya et al, 2021).…”
Section: Types Of Climate Actionmentioning
confidence: 99%
“…Maor anchors the analysis in two divergent phenomena. He distinguishes between unintentional, non-intentional and intentional disproportionality (Howlett & Kemmerling, 2017;Maor, 2017aMaor, , 2018Maor, , 2021Upadhyaya et al 2021). While intentional disproportionality is the result of some sort of error in the decision-making process, intentional disproportionality refers to situations in which policy makers deliberately overreach or underreact when addressing a problem.…”
Section: The Disproportionate Policy Making Thesis: Core Elements and Limitationsmentioning
confidence: 99%